Алгоритмы решения уравнения X - AᵀX⁻¹A = Q - Ларин, В.Б. (Проблемы управления и информатики, 2009)
Проаналізовано спектр матричного пучка, асоційованого з даним матричним рівнянням. На основі результатів аналізу запропоновано алгоритми побудови рішень цього рівняння. На прикладах проведено порівняння точності запропонованих алгоритмів та алгоритмів інших авторів. The analysis of a spectrum of the matrix pencil associated with the considered matrix equation is carried out. Being based on results of this analysis, algorithms of construction of the solutions of this equation are offered. On the examples, the comparison of accuracy of the offered algorithms and algorithms of other authors is carried out.